Enhancing the antimicrobial activity of eugenol, carvacrol and vanillin immobilised on silica supports against Escherichia coli or Zygosaccharomyces rouxii in fruit juices by their binary combinations. (October 2019) - Ribes, Susana; Ruiz-Rico, María; Pérez-Esteve, Édgar; Fuentes, Ana; Barat, José M.
Abstract: In this work, the antimicrobial activity and synergistic effect of eugenol, carvacrol and vanillin immobilised on MCM-41 microparticles against Escherichia coli and Zygosaccharomyces rouxii, on culture media and fruit juices, were investigated. Immobilised bioactive compounds exhibited great in vitro antimicrobial activity against the target microorganisms. Moreover, immobilised eugenol inhibited E. coli growth after its incorporation into grape juice, regardless of the tested concentration and storage time. Conversely, immobilised carvacrol and eugenol exhibited the greatest effectiveness in reducing fungi development in fruit juices. The immobilised eugenol and vanillin combination exhibited a non-interactive effect (1 < fractional inhibitory concentration index (FICi) ≤4) against E. coli . For Z. rouxii, a synergistic effect (FICi ≤ 0.5) between immobilised eugenol and carvacrol was observed in apple juice, whereas an additive effect (0.5 < FICi ≤1) was achieved by mixing these antimicrobial supports in grape juice. This work demonstrates the feasibility of combining functionalised antimicrobial devices to enhance the microbial stabilisation of fruit juices. Highlights: Antimicrobial activity of natural agents immobilised on silica supports was studied. Different combinations of immobilised eugenol, carvacrol and vanillin were tested. Mixtures of immobilised eugenol and carvacrol showed synergy in apple juice. The immobilisation reduced the aroma intensity of the antimicrobials used. The combinations of immobilised agents contributed to the juice preservation.